2020
DOI: 10.21475/ajcs.20.14.12.2721
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic correlations and path analysis between morphoagronomic and bromatological traits in corn hybrids for silage production

Abstract: The aim of this study was to estimate the correlation coefficients and slicing the phenotypic correlations into direct and indirect effects by path analysis between morphoagronomic and bromatological traits in corn hybrids for silage. Nineteen topcross hybrids and five controls were assessed in a randomized block design with four replications in two environments (Campos dos Goytacazes and Itaocara, RJ), in the 2013/2014 agricultural year. Phenotypic correlations and path analysis were estimated between morphoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…It is recommended to use regression models for bromatological variables when R 2 is higher than 0.70 (Paludo et al, 2020;Rodrigues et al, 2020). Previous studies in the literature have also reported trail analyses with R 2 values below 0.7, providing support for conducting this analysis (Crevelari et al, 2020;Ligoski et al, 2020).…”
Section: Bromatological Characteristicssupporting
confidence: 62%
“…It is recommended to use regression models for bromatological variables when R 2 is higher than 0.70 (Paludo et al, 2020;Rodrigues et al, 2020). Previous studies in the literature have also reported trail analyses with R 2 values below 0.7, providing support for conducting this analysis (Crevelari et al, 2020;Ligoski et al, 2020).…”
Section: Bromatological Characteristicssupporting
confidence: 62%
“…It is recommended to use regression models for bromatological variables when R 2 is higher than 0.70 (Paludo et al, 2020;Rodrigues et al, 2020). Previous studies in the literature have also reported trail analyses with R 2 values below 0.7, providing support for conducting this analysis (Crevelari et al, 2020;Ligoski et al, 2020).…”
Section: Bromatological Characteristicsmentioning
confidence: 89%
“…Potential hybrids for grain and silage production were selected from 72 corn strains in the state of Paraná in southern Brazil [10]. Morphoagronomic and bromatological characteristics were evaluated for 19 corn hybrids for silage in Rio de Janeiro state in southeast Brazil, with positive associations between dry matter yields and silage quality [27]. In Ethiopia, Africa, corn hybrids had better combined food-fodder traits [28].…”
Section: Introductionmentioning
confidence: 99%